Pemanfaatan Ikan Kakap Dan Daun Kelor Menjadi Hidangan Siomay - Tri Rettagung Diana; Renaldy Kresna P.P; Ira Handayani (Garina, 2023)
Siomay is a food originating from China which was brought to Indonesia which is then much loved by Indonesian people. Apart from mackerel, snapper fish can also be an alternative as a substitute for siomay raw materials. Vegetables that are usually used are carrots and leeks besides that Moringa leaves can also be an alternative to supporting ingredients. The aims of this study were (1) to determine the most preferred composition of snapper dumplings and moringa leaves. (2) To find out how to make snapper and moringa leaf dumplings. (3) To find out the public's acceptance of snapper and moringa leaf dumplings. The level of people's preference for snapper dumplings and Moringa leaves from the results of the questionnaire test showed that the panelists liked the aspects of taste, aroma, texture with the addition of 20%